The politics of numbers and additionality governing the national Payment for Forest Environmental Services scheme in Vietnam: A case study from Son La province - Thuy, Pham Thu; Chau, Ngo Ha; Chi, Dao Thi Linh; Long, Hoang Tuan; Fisher, Micah R. (Forestry Faculty, Universitas Hasanuddin, 2020)
Payments for forest environmental services (PFES) is a major breakthrough policy in the Vietnamese forestry sector because it contributes 25% of the total investments in the forestry sector and serves as the first market-based instrument employed to protect forests. However, there is little empirical evidence of its effectiveness. Is the policy meeting the core objectives of improving forest cover and forest quality and is it also achieving its claims of supporting local livelihoods? This paper analyses the environmental, social, and economic impacts of PFES in Son La province, the longest standing implementation of a PFES scheme in Vietnam. Our study uses a sampling method that incorporates pre-matching and a before-after-control-intervention approach. Data was collected from government statistics, remote sensing analysis, focus group discussions involving 236 people, surveys with a total of 240 households, and key informant interviews with 45 people. Our findings show that additionality of PFES in Son La is controversial and depends on who collects the data and what data is used to evaluate the impacts of PFES. Data collection is also politicized to serve central, provincial and district government interests. Evidence shows that PFES has provided little additional income to individual villagers to protect forests in Son La. However, total PFES revenue paid to communities generates significant income for village communities. Moreover, not all villagers can receive continuous payments from PFES, meaning that PFES has not become a stable source of income, rendering the permanence of PFES limited. Improving monitoring and evaluation policies coupled with transparent, inclusive, independent mechanisms are essential to providing a more accurate reflection of impacts from PFES in Vietnam.